2010
DOI: 10.1093/jmcb/mjq002
|View full text |Cite
|
Sign up to set email alerts
|

Cell-in-cell Structures Formed between Human Cancer Cell Lines and the Cytotoxic Regulatory T-cell Line HOZOT

Abstract: We previously established a novel cell line, termed HOZOT, derived from umbilical cord blood mononuclear cells that is characterized as a human cytotoxic regulatory T (Treg) cell line with a FOXP3(+)CD4(+)CD8(+)CD25(+) phenotype. Here, we describe a new property of HOZOT cells: they actively penetrate into a variety of human cancer cell lines, but not into normal cell lines, and form apparent cell-in-cell structures. In the process of cell penetration, we observed that HOZOT cells adhered to target cells seeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 31 publications
3
43
0
Order By: Relevance
“…Although the biological properties of cell-in-cell structures remain unclear, the cell-in-cell activity by which immune cells penetrate the cytoplasm of tumor cells has been shown to result in programmed cell-in-cell death45. HOZOT cells are a novel cord blood–derived line of Tregs that exhibit multiple properties, such as cytotoxic activity and cell-in-cell activity against human tumor cells5. These findings have led to considerable recent research exploring the therapeutic effects of combining HOZOT cells and oncolytic viruses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the biological properties of cell-in-cell structures remain unclear, the cell-in-cell activity by which immune cells penetrate the cytoplasm of tumor cells has been shown to result in programmed cell-in-cell death45. HOZOT cells are a novel cord blood–derived line of Tregs that exhibit multiple properties, such as cytotoxic activity and cell-in-cell activity against human tumor cells5. These findings have led to considerable recent research exploring the therapeutic effects of combining HOZOT cells and oncolytic viruses.…”
Section: Discussionmentioning
confidence: 99%
“…HOZOT cells were previously established from human umbilical cord blood6 and characterized as a cytotoxic Treg line with cell-in-cell activity5. HOZOT cells were maintained over mouse normal stromal ST2 cells (purchased from the RIKEN BioResource Center [Ibaraki, Japan]) and cultured in RPMI-1640 medium supplemented with 10% fetal bovine serum, 100 U/mL penicillin, and 100 mg/mL streptomycin.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Makoto Takeuchi et al also reported that HOZOT cells, a type of cytotoxic regulatory cells, actively penetrated into target tumor cells. It is proposed that HOZOT cells within tumor cells may exert a cytotoxic effect against the target cells partially via similar caspase-3 dependent pathway [11]. These results indicate that heterotypic cell-in-cell structures exhibit distinct biological characteristics and significance compared to entosis or cannibalism.…”
Section: Introductionmentioning
confidence: 95%